Understanding of the State Civil Apparatus on the Corruption Perception Index in Indonesia - Khumayah, Siti (Jurnal Polisci, 2024)
The role of Indonesian state civil servants (ASN) in combating corruption is covered in this article, with particular attention paid to how well they comprehend the Corruption Perception Index (GPA). This study, which used qualitative research methods, found that only a tiny portion of ASNs had a thorough comprehension of and ability to communicate GPA. ASN comprehension is impacted by several factors, including a lack of knowledge about the repercussions of neglecting one's GPA, a lack of training tools, and restricted information availability. Lower-level or regional civil officials frequently need more understanding, even though those working in the legal, judicial, and legislative sectors typically have a superior understanding. Thus, improving ASN's comprehension of GPA is essential to the government's anti-corruption initiatives. With increased knowledge, public employees will be better equipped to actively participate in efforts to stop and deal with corruption in Indonesia.